Fabrication of mesoporous TiO2/PVDF photocatalytic membranes for efficient photocatalytic degradation of synthetic dyes. Issue 4 (August 2021) - Erusappan, Elangovan; Thiripuranthagan, Sivakumar; Radhakrishnan, Ramakrishnan; Durai, Mani; Kumaravel, Sakthivel; Vembuli, Thanigaivel; Kaleekkal, Noel Jacob
Abstract: Water recovery and reuse are the two best alternatives to assuage the growing water scarcity. Mixed matrix membranes (MMMs) incorporated with heterogeneous photocatalysts have been proven to be efficient in the degradation of toxic organic compounds, particularly dyes. In this study, a mesoporous photocatalyst, titanium dioxide, was prepared using two different routes: (1) Solution combustion synthesis using different organic fuels such as (TiO2 -U), (TiO2 -G), (TiO2 -A), (TiO2 -H), and (TiO2 -HM); (2) Modified hydrothermal method using an abundantly available polysaccharide starch (TiO2 -S). These photocatalysts were exhaustively characterized to study their physicochemical and structural properties using XRD, UV-DRS, FT-Raman, BET, PL Spectra, XPS, HR-SEM, HR-TEM and EDX. The mesoporous TiO2 nanoparticles incorporated mixed matrix PVDF membranes were synthesized by the facile non-solvent induced phase separation technique. The photocatalytic activity of the synthesized catalysts and the MMMs were evaluated using two different dyes such as Congo Red (CR) and Reactive Yellow 145 (RY 145). As far as the catalyst embedded membranes are concerned, they also show a similar trend but slightly reduced photocatalytic activity. Among the MMMs, TiO2 –S/PVDF showed higher photocatalytic activity. The percentage decolourization/mineralization of CR and RY 145 over were determined to be 84%/71% and 100%/87% respectively. Kinetic studies revealed that among the synthesized catalysts, TiO2 -S/PVDF showed the highest kapp and the lowest t1/2 values – CR – 0.0061 min −1 and 113 min; RY 145 – 0.0134 min −1 and 51.71 min. The PVDF MMMs were also found to be thermally stable with excellent recyclability and long-term activity. Graphical Abstract: ga1 Highlights: Mesoporous TiO2 spheres were synthesized by solution combustion and modified hydrothermal methods. Mixed matrix PVDF membranes containing TiO2 catalyst were casted by the phase inversion technique. TiO2 -S/PVDF photocatalytic membranes showed the highest photocatalytic activity for the degradation of both CR and RY145 dyes. The reusability test revealed that the most active TiO2 -S/PVDF also showed the highest stability